A dança de salão como um dos conteúdos de dança na escola - Volp, Catia Mary [UNESP] (My University, 2010)
This paper presents the right all citizens have to dance. It focus on the official orientations which deals with dance as a legitimate content at school briefly discussing the difficulty to implement this content. Among various dance manifestations we highlight Ballroom Dance, its characteristics and benefits. We trace the historical path of Ballroom Dance in Brazil at colleges.
Ballroom dance as one of the dance contents at school
Keywords: Ballroom dances; Creative dance; Professional development